E-Monitoring of Asthma Therapy to Improve Compliance in children (e-MATIC): a randomised controlled trial. Issue 3 (26th May 2016) - Vasbinder, Erwin C.; Goossens, Lucas M.A.; Rutten-van Mölken, Maureen P.M.H.; de Winter, Brenda C.M.; van Dijk, Liset; Vulto, Arnold G.; Blankman, Ellen I.M.; Dahhan, Nordin; Veenstra-van Schie, Monique T.M.; Versteegh, Florens G.A.; Wolf, Bart H.M.; Janssens, Hettie M.; et al.
Real-time medication monitoring (RTMM) is a promising tool for improving adherence to inhaled corticosteroids (ICS), but has not been sufficiently tested in children with asthma. We aimed to study the effects of RTMM with short message service (SMS) reminders on adherence to ICS, asthma control, asthma-specific quality of life and asthma exacerbation rate; and to study the associated cost-effectiveness. In a multicentre, randomised controlled trial, children (aged 4–11 years) using ICS were recruited from five outpatient clinics and were given an RTMM device for 12 months. The intervention group also received tailored SMS reminders, sent only when a dose was at risk of omission. Outcome measures were adherence to ICS (RTMM data), asthma control (childhood asthma control test questionnaire), quality of life (paediatric asthma quality of life questionnaire) and asthma exacerbations. Costs were calculated from a healthcare and societal perspective. We included 209 children. Mean adherence was higher in the intervention group: 69.3% versus 57.3% (difference 12.0%, 95% CI 6.7%–17.7%). No differences were found for asthma control, quality of life or asthma exacerbations. Costs were higher in the intervention group, but this difference was not statistically significant. RTMM with tailored SMS reminders improved adherence to ICS, but not asthma control, quality of life or exacerbations in children using ICS for asthma. e-Monitoring with tailored SMS reminders improves adherence to ICS, but not clinical outcomes in children with asthma http://ow.ly/4mWMgx